Pengembangan Modul Pembelajaran Berbasis POE (Predict-Observe-Explain) Berbantuan Media Rolling Ball pada Materi Senyawa Hidrokarbon - Wardani, Alfida Fitri; Siahaan, Jeckson; Anwar, Yunita Arian Sani (Chemistry Education Practice, 2024)
The purpose of study was to develop a feasible and practical POE (Predict-Observe-Explain) based learning module assisted by rolling ball media on hydrocarbon compound properties. The study is a research and development study which uses a 4D model. The result of data analysis shows that the value of validity of the POE (Predict-Observe-Explain) based learning module assisted by rolling ball media on hydrocarbon compound properties using Aiken index was 0.84 in the category of very feasible. The practicality of the POE (Predict-Observe-Explain) based learning module assisted by rolling ball media on hydrocarbon compound properties is in the category of very practicality with a practical percentage of 87.25%. Based on the result, it can be concluded that the develop POE (Predict-Observe-Explain) based learning module assisted by rolling ball media on hydrocarbon compound  properties is feasible and practical use as an additional learning resource.